Effective synthesis of n-butyl salicylate over wash coated cordierite honeycomb by zirconia and its mixed oxides: a kinetic study - Shyamsundar, M; Shamshuddin, SZM (Bangladesh Journal of Scientific and Industrial Research, 2018)
Cordierite honeycombs were coated with solid acid catalysts such as ZrO2 (Z), Mo(VI)/ZrO2 (MZ) and Pt-SO4 2-/ZrO2 (PSZ) were prepared and characterized for their physico-chemical properties. These catalytic materials were characterized for their total surface acidity, crystallinity, functionality, elemental analysis and morphology by using techniques such as NH3 -TPD, PXRD, FTIR, ICP-OES, SEM and TEM respectively. These honeycomb catalysts were used for the liquid phase transesterification reaction of methyl salicylate (MS) with n-butanol (n-BA). Optimization of reaction conditions such as reaction temperature, reaction time, amount of catalysts and molar ratio of the reactants were carried out to obtain maximum yield of transester (n-butyl salicylate). n-butyl salicylate is obtained as major product and di-butyl ether is obtained as minor product. Highest total transester 70 % obtained by MZ and 80 % n-butyl salicylate and 10 % selectivity of di-butyl ether obtained in the presence of 0.4 g of honeycomb coated catalysts at a molar ratio of MS: n-BA 2:1, reaction temperature 403 K and reaction time 4 h. The energy of activation (16.81 and 14.92 kJ mol-1) and temperature coefficient (1.36 and 1.12) values of the MZ and PSZ were obtained from the kinetic studies. Pre-adsorption studies showed that the transesterification reaction methyl salicylate with n-butyl alcohol over honeycomb catalysts follows Langmuir-Hinshelwood mechanism. A reaction mechanism for transesterification is proposed based on the kinetic data. Reactivation and reusability studies of the honeycomb coated as well as powder form of catalysts up to 6 reaction cycles were also studied. Bangladesh J. Sci. Ind. Res.53(1), 63-76, 2018